The Tokyo War Crimes Tribunal: law, history, and jurisprudence - Cohen, David (Cambridge University Press, 2020)
Like its Nuremberg counterpart, the Tokyo Trial was foundational in the field of international law. However, until now, the persistent notion of 'victor's justice' in the existing historical literature has made it difficult to treat it as such. David Cohen and Yuma Totani seek to redress this by cutting through persistent orthodoxies and ideologies that have plagued the trial. Instead they present it simply as a judicial process, and in so doing reveal its enduring importance for international jurisprudence. A wide range of primary sources are considered, including court transcripts, court exhibits, the majority judgment, and five separate concurring and dissenting opinions. The authors also provide comparative analysis of the Allied trials at Nuremberg, resulting in a comprehensive and empirically grounded study of the trial. The Tokyo Tribunal was a watershed moment in the history of the Asia-Pacific region. This groundbreaking study reveals it is of continuing relevance today.